Developmental Integration and Industrialisation in Southern Africa - Alexander Rusero (African Journal of Political Science)
A corpus of literature emphasises the need for industrialisation and integration if states belonging to regional blocs aspire to prosper economically, politically, socially, technologically and culturally. In Southern Africa, gains have been made mainly in political cooperation and solidarity but remain desperately underdeveloped regarding regional integration. Yet, current realities made evident through the advent of Covid 19 pandemic, the ongoing climate change-induced crisis, the energy crisis and the vexing challenges of migration call for the urgent need for regions that ought to foster and prioritise developmental integration and industrialisation. The text, Developmental Integration and Industrialisation in Southern Africa by Siphumelele Duma exposes this glaring gap in the literature by taking stock of the developmental integration and industrialisation matrix of the region whilst at the same time proffering solutions on what needs to be done for the realisation of the critical goals of these notions.